Impaired fasting glycemia versus impaired glucose tolerance test. Perinatal results. Cienfuegos, 2016 - Cristóbal Jorge Torres González; Yaneris Vega Romero; Vivian Rosa Vázquez Martínez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: Impaired maternal glycemia figures can cause perinatal morbidity and mortality. The study of impaired fasting blood glucose in pregnant women is of relevant importance, due to its impact on perinatal outcomes; and it requires new analyzes, in correspondence with the current criteria. Objective: to compare perinatal results of pregnant women with impaired fasting glycaemia, with those of those who presented an impaired glucose tolerance test. Methods: a descriptive study was carried out in the obstetrics department of the Dr. Gustavo Aldereguía Lima Hospital, in Cienfuegos, from January to December 2016. A number of 144 pregnant women diagnosed with gestational diabetes mellitus, according to criteria of the World Health Organization were studied and were divided according to the diagnostic criteria in: patients with impaired fasting blood glucose and patients with impaired glucose tolerance test. Both groups were compared in terms of clinical variables and perinatal results. Square Chi was used (p <0.05) and the risk ratio was calculated (95 % CI). Results: the groups compared showed similar results in terms of age, body mass index, time of pregnancy at diagnosis, parity, treatment, gestational age at birth; as well as in the perinatal results: rate of labor induction and cesarean section, congenital malformations, fetal microsomia and low weight, neonatal asphyxia, neonatal ventilation and admission to neonatal intensive care. Conclusion: pregnant women with impaired fasting blood glucose showed clinical characteristics and perinatal results similar to pregnant women with impaired glucose tolerance test.